High Adventure Number 104 - Garange, John; Edited by Gunnison, John P. (London Adventure House, 2009)
Personal record of his mountaineering experiences that reached their climax in the conquest of Mt. Everest
Keywords: Asia--Mount Everest -- Mountaineering expeditions